A study of clinical presentation, precipitating factors, and predictors of severity among patients with acute exacerbation of COPD attending the Emergency department of a tertiary care center - Parajuli, Angana; Pandey, Nishant; Jha, Sulav Kumar; Dahal, Bistrit; Gautam, Shreya (Journal of Gandaki Medical College-Nepal, 2026)
Introduction: Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality worldwide. Acute exacerbations frequently lead to emergency visits and worsen patient outcomes. This study aimed to assess the clinical presentation, precipitating factors, and predictors of severity among patients with AECOPD (Acute exacerbation of chronic obstructive pulmonary disease). Methods: A descriptive cross-sectional study was conducted among 150 patients presenting with AECOPD to the emergency department of a tertiary care center in Pokhara, Nepal. Data on clinical features, risk factors, and investigations were collected and analyzed using SPSS 25.0. Multivariable logistic regression was used to identify predictors of ICU admission. Results: The mean age was 75.6±9.8 years, with female predominance 92(61.3%). Shortness of breath 147(98%) and cough 125(83.3%) were the most common symptoms. Recent upper respiratory tract infection 38(25.3%) was the most frequent trigger. ICU admission was required in 42(28%) of patients. Increased respiratory rate, lower oxygen saturation, cyanosis, and accessory muscle use were associated with severity. Respiratory rate, PaO₂, and serum creatinine were independent predictors of ICU admission. Conclusions: AECOPD mainly affects elderly patients and is commonly triggered by infections. Simple clinical and laboratory parameters can help identify severe cases early, allowing timely management and improved outcomes.